Switching From Originator Adalimumab to the Biosimilar SB5 in Patients With Inflammatory Bowel Disease: Short-term Experience From a Single Tertiary Clinical Centre - Lukas, Martin; Malickova, K; Kolar, M; Bortlik, M; Vasatko, M; Machkova, N; Hruba, V; Duricova, D; Lukas, Milan (Journal of Crohn's & colitis, 2020)
BACKGROUND AND AIMS: Patients' perspectives after switching from originator to biosimilar adalimumab have yet to be assessed. We evaluated the efficacy of switching from the originator adalimumab to a biosimilar compound [SB5] in patients with inflammatory bowel disease [IBD]. METHODS: Data on IBD patients who were switched from the originator to biosimilar adalimumab [SB5] at IBD Center ISCARE were analysed. Disease activity was assessed using standard clinical indices (Harvey-Bradshaw index [HBI] for Crohn's disease [CD] and partial Mayo score for ulcerative colitis [UC]), and laboratory parameters (C-reactive protein [CRP] and faecal calprotectin [FC]). Trough levels and anti-drug antibodies were measured. Patients were evaluated 10 weeks [W10] after the switch, and results were compared with the control group of patients on originator compound. RESULTS: A total of 93 patients switched to biosimilar adalimumab were included [CD 86%] and were matched to 93 controls for age, gender, diagnosis, and disease activity. There was no difference in the disease activity in either SWITCH or ORIGINATOR cohorts between Weeks 0 and 10. Similarly, no difference was found between cohorts at both prespecified time points. Moreover, no significant differences in CRP or FC concentrations were seen between W0 and W10 either in the SWITCH, or in the ORIGINATOR cohort [p >0.05]. Adalimumab serum trough levels remained stable after the switch. No new safety signals were detected. CONCLUSIONS: Our study confirmed that switching IBD patients from the originator adalimumab to a biosimilar compound [SB5] does not affect treatment efficacy.
Keywords: Feces; biosimilární léčivé přípravky; ulcerózní kolitida; C-Reactive Protein; stupeň závažnosti nemoci; Treatment Outcome; Antibodies; protilátky; Retrospective Studies; výsledek terapie; Adalimumab; inflammatory bowel disease; C-reaktivní protein; Middle Aged; gastrointestinální látky; mužské pohlaví; Gastrointestinal Agents; Crohnova nemoc; Adult; Leukocyte L1 Antigen Complex; adalimumab; leukocytární L1-antigenní komplex; Tertiary Care Centers; ženské pohlaví; Biosimilar Pharmaceuticals; feces; retrospektivní studie; Humans; lidé středního věku; Crohn Disease; Drug Substitution; centra terciární péče; dospělí; biosimilar; Female; Severity of Illness Index; Colitis, Ulcerative; lidé; Male; náhrada léků